2022
DOI: 10.3390/foods11182888
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Pilot Study on the Effects of Sarcocornia as a Salt Substitute in Arterial Blood Pressure and Vascular Function in Healthy Young Adults

Abstract: Previous studies have shown that excessive salt intake is strongly associated with high blood pressure (HT), vascular dysfunction, and the overall risk of cardiovascular diseases. The aim of this study was to evaluate Sarcocornia effectiveness as a salt substitute, addressing its effect on cardiovascular function in healthy young individuals. Thirty healthy participants, aged 18 to 26 years, were randomized into two groups: the control group (CG) and the intervention group (IG). The IG used Sarcocornia powder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…After carrying out the characterization of vascular physiology according to Pereira et al [3], we confirmed a significant decrease in BP values and improvement in PWV in the IG. Concerning the amount of sodium excreted in 24 h, as described by Pereira et al [3], the CG presented an average value of 8.4 ± 1.8 g/day before the intervention and 8.5 ± 2.4 g/day after the intervention, while the IG presented an average value of sodium excretion of 8.9 ± 2.1 g/day before the intervention, and after the consumption of S. perennis, the medium value became 7.2 ± 1.2 g/day, denoting a reduction in sodium excretion within the IG.…”
Section: Study Samplesupporting
confidence: 65%
See 4 more Smart Citations
“…After carrying out the characterization of vascular physiology according to Pereira et al [3], we confirmed a significant decrease in BP values and improvement in PWV in the IG. Concerning the amount of sodium excreted in 24 h, as described by Pereira et al [3], the CG presented an average value of 8.4 ± 1.8 g/day before the intervention and 8.5 ± 2.4 g/day after the intervention, while the IG presented an average value of sodium excretion of 8.9 ± 2.1 g/day before the intervention, and after the consumption of S. perennis, the medium value became 7.2 ± 1.2 g/day, denoting a reduction in sodium excretion within the IG.…”
Section: Study Samplesupporting
confidence: 65%
“…The study sample included 30 participants, all young people aged over 18 years old (medium de 20.4 ± 1.2), with 23.3% being male and 76.7% female (Table 1) [3]. This research project was approved by the Ethics Committee of the Polytechnic Institute of Coimbra (7/2019, approved on 18 September 2019) and conducted in accordance with all the principles of the Declaration of Helsinki [3]. The participants were randomly divided into two groups equally.…”
Section: Study Samplementioning
confidence: 99%
See 3 more Smart Citations